Current concepts in salvage procedures for failing microvascular flaps: is there a superior technique? Insights from a systematic review of the literature - Tröltzsch, Matthias; Tröltzsch, Markus; Probst, F. A.; Ristow, Oliver; Ehrenfeld, M.; Otto, S. (International journal of oral and maxillofacial surgery, 2016)
Microvascular free tissue transfer is a routine procedure with high predictability and a low complication rate. However, compromised flap perfusion remains a challenge and there is no consensus regarding the appropriate flap salvage protocol. The purpose of this study was to identify techniques with implications for flap salvage procedures and to assess their efficacy. A systematic review of studies published in the literature between 1990 and 2015, with predefined inclusion and exclusion criteria, was performed. The data obtained were pooled and analyzed. A total of 39 studies qualified for data extraction. The overall level of evidence was low and the total number of reported cases was limited (330 flaps). Five studies involved control groups and supplied comparative data. Surgical anastomotic revision and thrombectomy are inevitable in every flap salvage protocol. Four techniques or combinations of these with positive effects on flap salvage success rates were identified: thrombectomy with a Fogarty catheter (six studies, 68 flaps), intraoperative use of thrombolytic drugs (16 studies, 184 flaps), placement of an arteriovenous fistula (five case reports, five flaps), and the postoperative application of medicinal leeches (11 studies, 73 flaps). Currently available data exploring flap salvage procedures are limited. None of the techniques presented yielded superior salvage outcomes.